2021
DOI: 10.3389/fmicb.2021.674004
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic, Fungal, and Unicellular Eukaryotic Core Communities Across Three Sympatric Marine Sponges From the Southwestern Atlantic Coast Are Dominated Largely by Deterministic Assemblage Processes

Abstract: Marine sponges are known to harbor a diverse and complex microbiota; however, a vast majority of surveys have been investigating the prokaryotic communities in the north hemisphere and Australia. In addition, the mechanisms of microbial community assembly are poorly understood in this pivotal player of the ecosystem. Thus, this survey addressed the holobiome of the sponge species in the São Paulo region (Brazil) for the first time and investigated the contribution of neutral and niche processes of prokaryotic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 101 publications
(180 reference statements)
1
13
0
Order By: Relevance
“…As reported by Hardoim et al (2021) , prokaryotic communities associated with A. caissara and A. fulva were very similar among these two species and dominated by Chloroflexi, Proteobacteria, Crenarchaeota, and Acidobacteria. In contrast, in this study, Chloroflexi was only represented with a high relative abundance in 2-m Aplysina sp samples and Crenarchaeota did not represent an important component in any of the samples.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As reported by Hardoim et al (2021) , prokaryotic communities associated with A. caissara and A. fulva were very similar among these two species and dominated by Chloroflexi, Proteobacteria, Crenarchaeota, and Acidobacteria. In contrast, in this study, Chloroflexi was only represented with a high relative abundance in 2-m Aplysina sp samples and Crenarchaeota did not represent an important component in any of the samples.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, in this study, Chloroflexi was only represented with a high relative abundance in 2-m Aplysina sp samples and Crenarchaeota did not represent an important component in any of the samples. However, these same authors ( Hardoim et al, 2021 ) mentioned that community composition was largely different for Aplysina species. For instance, the most abundant phyla encountered in A. fulva, A. cauliformis, A. archeri, A. cavenicola , and A. aerophoba sampled in seven distinct sites were assigned to Proteobacteria, Chloroflexi, unclassified bacteria, Acidobacteria, and Actinobacteria ( Thomas et al, 2016 ), or A. fulva collected in Brazil with the community dominated by Cyanobacteria, Proteobacteria, and Chloroflexi ( Hardoim et al, 2009 ), which coincides with the phyla with the highest relative abundance in the 2-m Aplysina sp samples collected at Punta Arena BCS.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from environmental metagenomics, the study of organism-associated biomes (holobiomes) can provide an overview of organism–organism associations ( Hardoim et al, 2021 ) together with a snapshot of local viromes, as shown for the human virome ( Garmaeva et al, 2019 ; Koonin, Dolja & Krupovic, 2021 ). Perhaps this approach is suffering less from limitations relating to proper host assignation, although additional challenges should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Also, only Rodriguez-Marconi and collaborators included seawater samples in their experimental design. The approaches used in these studies directly impacts the understanding of the microeukaryotic community associated with these sponges, making comparisons difficult (Hardoim et al 2021). On the other side, these investigations have gathered further evidence that, just as occurs in the bacterial and archaeal communities, the protists associated with sponges can also possess host specificity.…”
Section: Approachesmentioning
confidence: 99%
“…Interestingly, in the sponge Acanthostylotella cornuta it was observed a high relative abundance of Metamonada, basal heterotrophic eukaryotes that are usually grazers of bacterial communities, but with parasitic representatives . In a more recent study (Hardoim et al 2021), again the question of microeukaryome specificity was raised. Although the previous studies are not directly comparable given methodological divergences, the investigation of the microeukaryotic community of three sympatric species from South America indicates that the hosts directly act on the selection of microorganisms.…”
Section: Approachesmentioning
confidence: 99%